Coal cleaning using jig and response surface approach for determination of quality of clean coal. Issue 2 (1st February 2020) - Kumar, Shravan; Venugopal, R.
ABSTRACT: Beneficiation of −10 + 3 mm size coking coal was carried out in three intermediate-size fractions: 10 + 6.73 mm, −6.73 + 4.73 mm, and −4.73 + 3 mm. Laboratory model Denver jig was used for the experiments with a target ash content of less than 17% in the clean coal product. Particle size, bed height, and jigging time were considered as process variables to analyze their effect on the performance of jig in terms of ash content of clean coal. Design of experiment was carried out using Taguchi approach which uses standard orthogonal arrays for forming a matrix of experiments. Influence of operating variables of the jig on responses was presented and discussed in 2D response surface plots. The model thus developed from the experimental results was found to be significant within the range of parameters under investigation with correlation of coefficient values as 0.99 for ash content. The ash content in the clean coal was found to be less than 17% for coals of less than about 5 mm, bed height about 40 mm. An increase in the jigging time was found to affect the performance only in the top layers of jig bed up to about 40 mm thick.